You are too Black - Mark S Mngomezulu (African Journal of Political Science)
This paper argues that xenophobia in South Africa is a result of intersecting historical, economic, and socio-political factors specific to the South African nationalist project embarked upon after independence. It will show how a confluence of the aforementioned factors in the country have, for the most part, contributed to an environment which is fertile for xenophobia and its expression through physical violence, especially towards other black Africans. This argument is significant because xenophobia is usually viewed from a resource scarcity perspective.